Bilateral Diaphragm Paralysis in Deep Neck Infection: Mimicking Respiratory Distress in Sepsis - Yakushiji, Tatsumi; Hakozaki, Takahiro; Iseki, Yuzo; Inoue, Satoki (Faculty of Medicine, Brawijaya University, 2024)
Background: This case report highlights an occurrence of bilateral diaphragm paralysis following surgical drainage for deep neck infection.Case: A 56-year-old male underwent surgical drainage and tracheostomy for a deep neck infection. Before the second surgical drainage, he exhibited tachypnea (>30 bpm), although his general condition was not significantly compromised. Following a successful drainage procedure, he was transferred to the intensive care unit and placed on mechanical ventilation. Despite attempts at spontaneous breathing trials (SBT), he failed each trial, leading to a deterioration in his general condition. Subsequently, he was diagnosed with diaphragm paralysis.Conclusion: The clinical manifestations of bilateral diaphragm paralysis closely resemble the common symptoms of sepsis. Therefore, it is crucial to recognize that surgical interventions for deep neck infections may pose a risk of developing diaphragm paralysis, likely associated with phrenic nerve palsy.